2000
DOI: 10.1515/ncrs-2000-0202
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of cobalt chromium germanium, CoCrGe

Abstract: CoCrGe, hexagonal, P^mmc (No. 194), a = 4.092(1) Ä, c = 5.145(2) Ä, V= 74.6 Ä 3 , Z= 2, R e (F) = 0.049, wR m (F 2 ) = 0.097, Γ= 300 K. Source of materialSingle crystals of cobalt chromium germanium were grown by chemical vapour transport in a closed quartz ampoule. Iodine was used as transporting agent. The metals and the transporting agent were heated at 1148 Κ for seven days to homogenize the source material. The chemical vapour transport was performed at 1073 Κ -> 1223 Κ. After seven days, the deposition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…All the diffraction peaks can be indexed with a hexagonal structure, and the lattice parameters of a and c are 4.092 (1) Å and 5.145 (2) Å, respectively. Further analysis found that this new phase is isostructural to the hexagonal structure of CrCoGe reported before [23], which has a space group of P6 3 /mmc.…”
Section: Crystal Structural Evolutionsupporting
confidence: 56%
“…All the diffraction peaks can be indexed with a hexagonal structure, and the lattice parameters of a and c are 4.092 (1) Å and 5.145 (2) Å, respectively. Further analysis found that this new phase is isostructural to the hexagonal structure of CrCoGe reported before [23], which has a space group of P6 3 /mmc.…”
Section: Crystal Structural Evolutionsupporting
confidence: 56%
“…. For CoCrGe, CoFeGe, FeMnGe, FeMnP and FeCrAs, the ground state is hexagonal Ni 2 In structure [27][28][29][30]. Their metastable energies for the half-Heusler structure are 0.14, 0.18, 0.22, -0.02 and -0.54 eV, respectively.…”
Section: (B)mentioning
confidence: 99%
“…Nine half-Heusler half-metals are predicted with the half-metallic gap of 0.07-0.67 eV. In fact, most of these nine compounds crystallize in hexagonal Ni 2 In structure in the bulk form [27][28][29][30], and some of them exhibited the property of phase transformation, forming orthorhombic TiNiSi structure [31][32][33][34][35]. In order to investigate the possibility of experimentally fabrication of these half-Heusler half metals, we further reveal from the structural stability that the formation energies for these nine half-Heusler compounds are negative, thus suggesting a possibility of synthesizing these half-metals in the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…9 On the contrary, it has been seen in the literature that many of the half Heusler alloy samples exhibit non-cubic symmetries but there is no explicit discussion on the half-metallicity in these materials. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] It has been observed that NiMnSb and some other ABSb, as well as ABSn materials possess cubic C1 b symmetry. 24 On the other hand, while NiMnGe is seen to exhibit an orthorhombic P nma space-group at room temperature, 25 NiMnGa has a hexagonal symmetric structure.…”
Section: Introductionmentioning
confidence: 99%
“…20 Further, ABSi or ABGe or ABP or ABAs compounds are seen to exhibit either an orthorhombic structure (with P nma space-group) or a hexagonal phase (with either P 6 3 /mmc or P 62m space-group). [10][11][12][13][14][15][16][17][18][19][20][21][22][23] In the literature, there are also reports that, many samples of HHAs are seen to exhibit more than one symmetries. For example, each of NiMnAs and NiMnP are reported to possess both orthorhombic and hexagonal structures.…”
Section: Introductionmentioning
confidence: 99%